Waste-Based Second-Generation Bioethanol: A Solution for Future Energy Crisis - Chandrasiri, Yasindra Sandamini; Weerasinghe, W. M. Lakshika Iroshani; Madusanka, D. A. Tharindu; Manage, Pathmalal M. (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The demand for more environmentally friendly alternative renewable fuels is growing as fossil fuel resources are depleting significantly. Consequently, bioethanol has attracted interest as a potentially viable fuel. The key steps in second-generation bioethanol production include pretreatment, saccharification, and fermentation. The present study employed simultaneous saccharification and fermentation (SSF) of cellulose through bacterial pathways to generate second-generation bioethanol utilizing corncobs and paper waste as lignocellulosic biomass. Mechanical and chemical pretreatments were applied to both biomasses. Then, two bacterial strains, Bacillus sp. and Norcadiopsis sp., hydrolysed the pretreated biomass and fermented it along with Achromobacter sp., which was isolated and characterized from a previous study. Bioethanol production followed by 72 h of biomass hydrolysis employing Bacillus sp. and Norcadiopsis sp., and then 72 h of fermentation using Achromobacter sp. Using solid phase micro extraction combined with GCMS the ethanol content was quantified. SSF of alkaline pretreated paper waste hydrolysed by Bacillus sp. following the fermentation by Achromobacter sp. showed the maximum ethanol percentage of 0.734Â±0.154. Alkaline pretreated corncobs hydrolyzed by Norcadiopsis sp. yielded the lowest ethanol percentage of 0.155Â±0.154. The results of the study revealed that paper waste is the preferred feedstock for generating second-generation bioethanol. To study the possible use of ethanol-diesel blends as an alternative biofuel E2, E5, E7, and E10 blend emulsions were prepared mixing commercially available diesel with ethanol. The evaluated physico-chemical characteristics of the ethanol-diesel emulsions fulfilled the Ceypetco requirements except for the flashpoint revealing that the lower ethanol-diesel blends are a promising alternative to transport fuels. As a result, the current study suggests that second generation bioethanol could be used as a renewable energy source to help alleviate the energy crisis..